Factors Influencing Students' Pro-Environmental Behavior: A Systematic Literature Review - Pratama, Sisi Hernanda; Ristanto, Rizhal Hendi; Handayani, Tri; Sigit, Diana Vivanti; Komala, Ratna (Biosfer: Jurnal Tadris Biologi, 2024)
Pro environmental behavior refers to individual efforts to protect the environment and minimize activities that can have a negative impact on the environment. The purpose of this research is to review the results of research on factors that influence students' pro-environment behavior. This research used the SLR method on articles sourced from National and International databases and obtained 20 articles published in 2019-2023. The results of the article analysis show that the factors that influence students' pro-environmental behavior are divided into 3 components, namely: 1) Socio-Demographic Factors (age, gender), 2) Internal Factors (Knowledge, Attitudes, Psychology, Values) and 3) External Factors ( Economic and Social Norma). Most research is carried out to examine students' pro-environmental behavior, namely knowledge, attitudes, gender and attitude factors. Further research is recommended to look at the influence of each factor to find out the strongest predictors so as to increase students' pro-environmental behavior.ABSTRAK: Perilaku pro lingkungan mengacu pada upaya individu untuk menjaga lingkungan dan meminimalkan kegiatan yang dapat berdampak negatif terhadap lingkungan.Tujuan penelitian ini untuk mereview hasil penelitian-penelitian tentang faktor-faktor yang mempengaruhi pro lingkungan siswa. Penelitian ini menggunakan metode SLR pada artikel-artikel yang bersumber dari database Nasional dan Internasional dan diperoleh 20 artikel yang diterbitkan pada tahun 2019-2023. Hasil analisis artikel menunjukan faktor-faktor yang mempengaruhi perilaku pro lingkungan siswa dikelompokkan menjadi 3 komponen yaitu: 1) Socio-Demographic factors (age, gender), 2) Internal Factors (Knowledge, Attitude, Psychology, Personal Norma) dan 3) External Factors (Economic and Social Norma). Penelitan paling banyak dilakukan untuk meneliti perilaku pro lingkungan siswa yaitu faktor pengetahuan, sikap, jenis kelamin dan sikap. Penelitian lebih lanjut disarankan melihat pengaruh dari masing-masing faktor untuk mengetahui prediktor yang paling kuat sehingga mampu meningkatkan perilaku pro lingkungan siswa.